Analisis Perbandingan Sitomorfometrik Apusan Bukal pada Perokok dan Non Perokok - Nadhira Siti Fauziah; Yuktiana Kharisma; Abdul Hadi Hassan (Bandung Conference Series: Medical Science, 2024)
Abstract. Cigarettes contain harmful substances, mainly nicotine, tar and carbon monoxide (CO) which are also carc5inogenic. Chemical substances in cigarettes can cause cellular changes in the oral mucosa if exposure is repeated and occurs continuously, the high prevalence of smoking causes an increased risk of diseases such as heart problems, oral cancer, nasopharyngeal cancer, and lung cancer. The incidence of oral cancer in smokers can be prevented by identifying cellular changes in the oral mucosa, one of which is quantitative microscopic observation, namely cytomorphometrics. Cytomorphometrics is a technique to identify and measure cell specifications including nucleus diameter, cytoplasmic diameter, and nucleus-cytoplasmic ratio. The purpose of this study was to compare the cytomorphometrics of buccal mucosal smears between smokers and non-smokers. This study used an analytic observational method through a cross-sectional approach, involving 42 subjects who were smokers and non-smokers. Epithelial smears were made from buccal swabs and stained using papanicola staining with the intention of knowing the cytomorphometric comparison of buccal mucosal smears between smokers and non-smokers in the Bandung Islamic University (UNISBA) environment. The results showed that there was a significant cytomorphometric comparison of buccal mucosa smears in smokers and non-smokers, where the average diameter of epithelial cell nuclei was higher in active smokers compared to the average of non-smokers. On the other hand, the mean cytoplasmic diameter was lower in active smokers compared to non-smokers, and for the nucleus/cytoplasm ratio the probability value was 0.000 (p < 0.05), respectively, indicating a significant difference in nucleus size and N/S ratio between smokers and non-smokers, which was higher in smokers. Abstrak. Rokok mengandung zat-zat berbahaya utamanya adalah nikotin, tar dan karbon monoksida (CO) yang juga bersifat karsinogenik. Zat kimia pada rokok dapat menyebabkan perubahan seluler pada mukosa mulut jika paparan berulang dan terjadi terus menerus, tingginya prevalensi merokok menyebabkan meningkatnya risiko terjadinya penyakit seperti gangguan jantung, kanker mulut, kanker nasofaring, dan kanker paru. Kejadian kanker mulut pada perokok dapat dicegah dengan mengidentifikasi perubahan seluler pada mukosa mulut salah satunya dengan pengamatan mikroskopis kuantitatif yaitu sitomorfometrik. Sitomorfometrik adalah teknik untuk mengidentifikasi dan mengukur spesifikasi sel meliputi diameter nukleus, diameter sitoplasma, dan rasio nukleus-sitoplasma. Tujuan penelitian ini adalah untuk membandingkan sitomorfometrik apusan mukosa bukal antara perokok dan non-perokok. Penelitian ini menggunakan metode observasional analitik melalui pendekatan cross-sectional, dengan melibatkan 42 subjek yang merupakan perokok dan non-perokok. Apusan epitel dibuat dari usap bukal dan diwarnai menggunakan pewarnaan papanicola dengan maksud untuk mengetahui perbandingan sitomorfometrik apusan mukosa bukal antara perokok dan non-perokok di lingkungan Universitas Islam Bandung (UNISBA). Hasil penelitian menunjukkan terdapat perbandingan sitomorfometrik apusan mukosa bukal yang signifikan pada perokok dan non-perokok, dimana rata-rata diameter nukleus sel epitel lebih tinggi pada perokok aktif dibandingkan dengan rata-rata non-perokok. Di sisi lain, rata-rata diameter sitoplasma lebih rendah pada perokok aktif dibandingkan dengan non-perokok, dan untuk rasio perbandingan nukleus/sitoplasma nilai probabilitas masing-masing adalah 0,000 (p < 0,05), menunjukkan perbedaan yang signifikan dalam ukuran inti dan rasio N/S antara perokok dan non-perokok, yaitu lebih tinggi pada perokok.